(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
When Carlos Droguette writes the feuilleton Dubois, a crime artist in 1946, has already published The Murdered of Seguro Obrero, a text that denounces the massacre of a group of young people by the forces of order, in Santiago de Chile, in 1938. The profession of journalist that the author practiced at that time placed him at the heart of current events and makes him sensitive to the events that make up the big headlines in the press. Along with the aforementioned works, the novel Eloy, from 1954, is also inspired by an event that impacted C.Droguette. The photograph of Bandit Eloy, riddled with bullets, on the first page of a newspaper left a deep mark on the writer. It is not surprising, therefore, that these three texts have given rise to one or several rewritings by the writer, which allows us to say that they accompanied him throughout his life.